2001
DOI: 10.1002/1529-0131(200103)44:3<541::aid-anr102>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Lymph draining from foot joints in rheumatoid arthritis provides insight into local cytokine and chemokine production and transport to lymph nodes

Abstract: Objective Rheumatoid arthritis (RA) is characterized by inflammatory reactions in joints and adjacent tissues unaccompanied by clinically evident changes in lymphatics and lymph nodes draining the inflamed areas. The explanation for this phenomenon, which contrasts with infectious processes in joints and soft tissues that evoke major changes in the lymphatic system, is unclear. To determine which inflammatory factors produced in the joints of RA patients are transported in lymph to lymph nodes, we measured lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 29 publications
3
47
0
1
Order By: Relevance
“…This vessel was cannulated and lymph was collected by retrograde flow over 24 h (to minimize differences in capillary filtration rate due to positioning effects) into heparinized tubes at 2-h intervals as described (15,16). All human subject experiments were performed with the approval of institutional authorities by two of the authors (W.L.O.…”
Section: Measurement Of Ccl27 In Human Lymphatic Fluidmentioning
confidence: 99%
“…This vessel was cannulated and lymph was collected by retrograde flow over 24 h (to minimize differences in capillary filtration rate due to positioning effects) into heparinized tubes at 2-h intervals as described (15,16). All human subject experiments were performed with the approval of institutional authorities by two of the authors (W.L.O.…”
Section: Measurement Of Ccl27 In Human Lymphatic Fluidmentioning
confidence: 99%
“…By making the (31,27). In order to achieve a steady-state interstitial space: plasma ratio as high as 0.17 it was necessary to use a reflection coefficient of 0.62.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline plasma level of TNF-α in subjects with rheumatoid arthritis (R max =4.4E-6 μM; CV 30%) and values for the degradation rate of TNF-α (k deg ) (0.877 1/h; CV 30%) were taken from published values (27,28). The TNF-α synthesis rate (k syn ) was calculated for each subject using the relationship R max ×k deg , and the degradation of the adalimumab-TNF-α complex was assumed to be the same as the degradation rate of endogenous TNF-α.…”
Section: Population Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, Olszewski et al [24] reported to have found that the average lymph flow rate from cannulated prenodal lymphatic vessels in RA patients doubled as compared with healthy individuals in the control group. They reported the standard cell concentration in the lymph to be 5-120/µl and double in RA patients.…”
Section: R Ry Yc C 3 3 Błona Maziowa Z Przerośniętą Warstwą Kommentioning
confidence: 99%